ARTERIAL WALL OF THE ALBINO RAT: MORPHOMETRIC STRUCTURE AND GENERAL MORPHOPHYSIOLOGY (Veterinária Notícias, 2015)
The histological structure and some morphometric parameters referring the aortic architecture of the adult, laboratorial albino rat were focused from the three segmental parts of the aorta comprising the thoracic ascendant and thoracic descendant parts, and the abdominal infra kidneys part of aorta. This last aortic segment showed a mixed pattern from the mural building formed by similar amounts of smooth muscle cells and connective matrix elements, being represented by collagen and elastic lamellae and fibers. However a classic elastic mural pattern was verified in the thoracic segments of the rat aorta, an intermingled pattern mainly occurred between the smooth muscle cells and matrix elements in all the segments of the rat aorta. The thickness of the aortic wall showed a numeric progressive lower from the ascendant part to the abdominal distal part of aorta. Similar pattern was verified for the number of elastic lamellae, which the major lamellar number observed could be related with the luminal vortex flow observed inside the ascendant aortic part. Also the aortic diameters verified decreased progressively from the ascendant to the abdominal part of aorta.